2004
DOI: 10.1017/s0033291704003745
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions and classes of psychosis in a population cohort: a four-class, four-dimension model of schizophrenia and affective psychoses

Abstract: Both dimensional and categorical approaches are useful in tapping the latent constructs underlying psychosis. Broad agreement with other similar studies suggests such findings could represent discrete pathological conditions. The four classes described appear meaningful, and suggest that the term non-affective psychosis should be reserved for the disorganization class, which represents only a subgroup of those with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 60 publications
0
59
0
1
Order By: Relevance
“…The 5 symptom dimensions reported in the present study agree with the findings from factor analyses in patient samples. 25,26 Although others have reported a 4 instead of a 5-factor solution [27][28][29] , this is mainly due to difficulties in separating the negative and disorganization dimensions. 30 Previous studies on subtypes of psychotic disorder have identified more psychotic clusters than we report in our study 8,[31][32][33] , although there is agreement with the class solution presented here.…”
Section: Discussionmentioning
confidence: 98%
“…The 5 symptom dimensions reported in the present study agree with the findings from factor analyses in patient samples. 25,26 Although others have reported a 4 instead of a 5-factor solution [27][28][29] , this is mainly due to difficulties in separating the negative and disorganization dimensions. 30 Previous studies on subtypes of psychotic disorder have identified more psychotic clusters than we report in our study 8,[31][32][33] , although there is agreement with the class solution presented here.…”
Section: Discussionmentioning
confidence: 98%
“…Factor scores have the potential advantages of being pseudo-continuous and allowing symptom weightings. However, in our view, these were outweighed by OPCRIT factor scores being highly dependent on which symptoms are included and having complex solutions that vary between samples [Cardno et al, 1997[Cardno et al, , 1999a[Cardno et al, , 2001Serretti et al, 2001;Murray et al, 2005;Dikeos et al, 2006], causing problems for interpreting and replicating results. Additionally, the phenotypic properties of symptom score dimensions have been investigated in detail in this sample [Cardno et al, 2008], and are more convenient when adjusting for ascertainment and assessing inter-rater reliability.…”
Section: Limitationsmentioning
confidence: 90%
“…Dimensional phenotypes often include more than two items/ symptoms but, in this particular context, the results of factor analyses are clearer and more consistent for small numbers of broad psychotic symptoms [Liddle, 1987;Andreasen et al, 1995;Peralta et al, 1997;Ratakonda et al, 1998] than larger numbers of symptoms [Cardno et al, 1997[Cardno et al, , 1999a[Cardno et al, , 2001Serretti et al, 2001;Murray et al, 2005;Dikeos et al, 2006], and within-pair correlations reduce as further symptoms are added to those analyzed here [Cardno et al, 2008].…”
Section: Limitationsmentioning
confidence: 99%
“…[21,25], factor analysis, e.g. [11,13], latent class analysis [1,31], or grade-of-membership models [19,26]. The method [14] that is presented in this study does not attempt a priori to identify clusters, categories or dimensions, but rather depicts the relations between objects in a Euclidean space in a structurally neutral way.…”
Section: Introductionmentioning
confidence: 99%